2023
DOI: 10.3390/jcm12237431
|View full text |Cite
|
Sign up to set email alerts
|

Consultation-Based Deprescribing Service to Optimize Palliative Care for Terminal Cancer Patients

Minoh Ko,
Sunghwan Kim,
Sung Yun Suh
et al.

Abstract: (1) Background: A pharmacist-led deprescribing service previously developed within the Consultation-Based Palliative Care Team (CB-PCT) was implemented for terminal cancer patients. (2) Objective: To evaluate the clinical outcomes of the developed deprescribing service for terminal cancer patients in CB-PCT. (3) Methods: A retrospective analysis compared the active care (AC) group to the historical usual care (UC) group. The clinical outcomes included the deprescribing rate of preventive medications, the propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Patients with terminal cancer have a life expectancy of less than 6 months and often face many comorbidities and systemic symptoms (Ko et al, 2023). Pain is one of the most common and intractable symptoms of terminal cancer, with an incidence rate of 66.4% (Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with terminal cancer have a life expectancy of less than 6 months and often face many comorbidities and systemic symptoms (Ko et al, 2023). Pain is one of the most common and intractable symptoms of terminal cancer, with an incidence rate of 66.4% (Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature has also revealed that the introduction of home services was associated an increase in the number of cancer patients dying in their homes, suggesting an escalation in the use of home services among terminally ill cancer patients[17]. Regarding consultation-based care, considering that this service delivers hospice care to patients who prefer not to be admitted to a hospital ward or are waiting admission, its increasing utilization reflects its potentially significant role in the provision of hospice services in healthcare facilities without a hospice ward or in serving as a bridge to facilitate access to inpatient care[18]. The fact that the number of patients who used both inpatient and consultation-based services showed an escalating trend during the study period reinforces the role of consultation-based services in transferring patients to inpatient care, suggesting the need to prepare for the potentially growing demand for consultation-based care in the future.…”
mentioning
confidence: 99%